Pengendalian Tindakan Phubbing Anak: Studi Analisis Peran Orang Tua Dalam Pola Asuh Anak Sekolah Dasar - Hidayat, Wahyu (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2023)
The purpose of this study is to explain the importance of the role of parents in controlling children's phubbing actions, as well as familiarizing children in using smartphones wisely. This type of research is field research with descriptive approach. The subjects in this study included parents who had early childhood and elementary school with a total of 12 people (5 Male, 7 Female). There are two data collection techniques conducted by researchers, namely (1) observation techniques, (2) interviews. Data testing techniques to verify the validity of data in this study include extension of participation, persistence of observation, and triangulation of methods. The results of the research showed that parents complain about the lack of communication with their children when their children use gadgets and many children do not care about their parents' calls when using gadgets. Solutions to research problems, the role of parents in supervising and accompanying children in the use of gadgets, as follows: 1) parents need to set a time limit when using technology to work or enjoy entertainment, and do not violate it, 2) parents accompany the child when using gadgets, 3) balance smartphone users with other activities, such as playing outdoors, 4) set smartphone rules (length of use and visible content), 5) parents as suri tauladan their children, as well as explaining content that should not be seen and accessed.